Clinical And Pathophysiological Perspectives On Felty Syndrome: Implications For Advanced Healthcare Practice (The Review of Diabetic Studies, 2024)
Background: Felty syndrome is a rare but severe extra-articular complication of long-standing seropositive rheumatoid arthritis (RA), classically defined by the triad of RA, neutropenia, and splenomegaly. Its pathogenesis reflects complex immune dysregulation, genetic predisposition—particularly HLA-DR4—and impaired neutrophil homeostasis.Aim: This review aims to synthesize current clinical, genetic, and pathophysiological knowledge about Felty syndrome and highlight implications for advanced nursing practice and multidisciplinary management.Methods: A comprehensive analysis of epidemiological data, immunogenetic studies, pathophysiological mechanisms, diagnostic strategies, and management approaches was conducted based on existing clinical research and observational evidence summarized in the article.Results: Findings indicate strong genetic associations with HLA-DRB1*0401, a prevalence of 1–3% among RA patients, and a typical latency of over 16 years after initial RA diagnosis. Pathophysiology involves impaired granulopoiesis, splenic sequestration, autoantibodies against G-CSF, and overlap with large granular lymphocyte (LGL) leukemia. Diagnosis requires integration of hematologic, immunologic, imaging, and bone marrow findings. Management relies on methotrexate as first-line therapy, rituximab for refractory disease, and G-CSF for severe neutropenia, with splenectomy reserved for selected cases.Conclusion: Felty syndrome represents a complex immuno-hematologic condition requiring early recognition, interprofessional collaboration, and individualized therapeutic strategies. Advances in DMARDs, biologics, and neutropenia management have substantially improved outcomes, although infection risk remains a major concern.